Disaster Mitigation Education for Children and Adolescents in Banda Aceh City - Putri Azhari; Nurul Kamaly; Afrijal; Wais Alqarni (Dedikasi Sosial: Jurnal Pengabdian Masyarakat, 2025)
This study aims to develop an effective disaster mitigation education model for children and adolescents in Banda Aceh City, focusing on enhancing awareness and preparedness against the threats of earthquakes and tsunamis. A qualitative research method was applied, utilizing contextual and emic approaches, combined with role-playing and various interactive media such as animations, educational games (SERGANA), disaster-themed songs, disaster simulations, and short educational videos. The program was implemented in several primary and secondary schools across Banda Aceh. The results indicate a significant improvement in students’ understanding of mitigation steps, risk awareness, and emergency decision-making abilities. These findings suggest that engaging and adaptive educational approaches can effectively foster a culture of disaster awareness from an early age.